The effect of extraction methods on total phenolics and antioxidant activities in Caulerpa racemosa (Forsskal) J. Agardh extracts - Sherley; Ni Putu Ermi Hikmawanti; Agustin, Mutia (Vitae, 2023)
Background: The edible green algae Caulerpa racemosa (Forsskal) J. Agardh (Caulerpaceae), also known as “sea grape”, is an excellent source of phenolic compounds known for their activity to reduce free radicals. Objectives: The research aims to evaluate the total phenolic content and antioxidant activity of C. racemosa (70% ethanol extracts) obtained from different extraction methods, such as maceration, Soxhlet, and ultrasound. Methods: Total phenolics of the extracts were determined by the colorimetry method using the Folin-Ciocalteu reagent. Total phenol content was expressed as mg gallic acid equivalent (GAE) per g extract. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical was used to assess the antioxidant activity of the extracts. Results: the ethanol extract of C. racemosa obtained from the ultrasonic methods had the highest phenolic content (39.38 mg GAE/g) compared to other extraction methods (Soxhlet was 37.31 mg GAE/g and maceration was 22.05 mg GAE/g). The IC50 value against DPPH of the C. racemosa ethanol extracts using ultrasonic, Soxhlet, and maceration was 352.95, 365.73, and 375.84 μg/mL, respectively. Conclusions: the variation of the extraction methods affected the total phenolics content of C. racemosa ethanol extracts and their antioxidant activity. We reported here the potential of C. racemosa extracts as an antioxidant raw material from marine plants for medicinal, nutraceutical, cosmetics, and food products; however, more research is needed.